The Intervention of Dialectical Behavior Therapy by Educational Psychology for Post-Traumatic Stress Disorder in College Students during the COVID-19 Epidemic - Chenyang Xiao, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
College students' psychological state was generally poor during the epidemic, particularly regarding dialectical behavior and depressed mood, which should be handled with counselling and intervention. This work aims to scientifically understand the psychological abnormalities of college students during the coronavirus disease 2019 (COVID-19) pandemic, and use scientific methods to actively intervene. It also intends to make college students relieve the tension and fear under the influence of COVID-19, adapt to their studies and life under epidemic management as soon as possible, and return to a rational and normal life. The intervention research on Post-traumatic stress disorder (PTSD) of college students is carried out. Firstly, it discusses the psychological problems and stress responses of college students during the COVID-19 epidemic. Secondly, it describes the methods of psychological intervention for college students through Dialectical Behavior Therapy (DBT) of educational psychology. Finally, the questionnaire survey method is used to analyse the impact of the epidemic on the psychology of college students, as well as the changes in PTSD symptoms during the psychological intervention of DBT. The results manifest that under the COVID-19 epidemic, the main traumatic events and stressful events suffered by college students come from the catastrophic events and violent events caused by the epidemic. During the epidemic, family pressure and personal academic pressure have become traumatic stressors for college students. The epidemic has posed a certain threat to college students' emotional disorders. College students may experience poor sleep, leading to emotional distress, anxiety, daze, and boredom. DBT has a significant intervention effect on the symptoms of PTSD in college students after the epidemic, which increases the score of college students' post-traumatic psychological growth (PTPG) by 21.52%, and plays a positive intervention role. This research has a certain reference to the psychological intervention of college students' PTSD during the COVID-19 epidemic.